2013
DOI: 10.1007/s10549-013-2669-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of referral for genetic counseling and testing in BRCA1/2 and Lynch syndromes: a nationwide study based on 240,134 consultations and 134,652 genetic tests

Abstract: Based on nationwide data from the French national cancer institute (INCa), we analyzed the evolution of cancer genetics consultations and testing over time, and the uptake of targeted tests in relatives of families with BRCA1/2 or MMR genes mutation. Genetic testing and consultations for familial high-risk individuals are exclusively funded and monitored by the INCa in France. All nationwide cancer genetics centers reported annually standardized parameters of activity from 2003 to 2011. The analysis included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 36 publications
1
45
1
Order By: Relevance
“…A recent survey in the United States revealed that only 19% of primary care physicians accurately assessed family history for BRCA1/BRCA2 testing (25). In BRCA1/ BRCA2 families in France, most eligible relatives are not referred for testing (26). In the present study in Israel, only 35% (29 of 82) of high-cancer-incidence families had been referred previously for genetic counseling, despite its availability within the Israeli universal single-payer health care system.…”
Section: Discussioncontrasting
confidence: 58%
“…A recent survey in the United States revealed that only 19% of primary care physicians accurately assessed family history for BRCA1/BRCA2 testing (25). In BRCA1/ BRCA2 families in France, most eligible relatives are not referred for testing (26). In the present study in Israel, only 35% (29 of 82) of high-cancer-incidence families had been referred previously for genetic counseling, despite its availability within the Israeli universal single-payer health care system.…”
Section: Discussioncontrasting
confidence: 58%
“…Breast, ovarian and colorectal cancer referrals made up over 90% of cancer in a descriptive study of referrals to cancer genetics services in the UK 26 with a figure of 82.2% in a similar analysis of French services. 27 In both reports, breast and bowel cancer accounted for around 60% and 20% of referrals, respectively. Breast, colorectal and NMSC were among the five most frequent tumours, an observation that is also seen in the UK population.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, there may be differences in rates of referral depending on the syndrome itself or the organ primarily affected by the syndrome. Previous studies assessing other hereditary cancer syndromes have suggested under-referral for Lynch syndrome genetic counseling versus BRCA1/2 genetic testing in patients with gynecologic cancer (20). Additionally, the uptake of genetic counseling has been shown to be lower in patients with EC versus those with ovarian cancer (21).…”
Section: Discussionmentioning
confidence: 99%